Literatura e educação :ação argumentativa na discussão de histórias - Freitas, Alessandra Cardozo de (2005)
The focus of this thesis is the discussion of stories from the fairy tales genre in reading classes of Children´s Literature. Its main purpose is to investigate the argumentative action in the mediation pedagogic process.The evidence from this study is that the argumentative action is a fundamental component of teacher´s mediation as far as story discussion is concerned. The concept of mediation in this thesis comes from principles of interacionist Psychology articulated with THE theory of argumentation. It is understood that argumentative action is a process that objectives to obtain and to intensify the interlocuter´s adhesion through speech. The analysis of the story discussion activity is based on Psycholinguistic, particularly on the study of prevision ability; on the Theory of reception with special reference to the theory of the aesthetic effect, which considers the reader´s reactions and reader´s replies to the text; and on sociocognitive conflict study highlighting conflicts modalities brought up by the discussion of texts. The corpus analysed is composed by discussion episodes of stories from reading classes of Children´s Literature realized through participative observation.The subjects were children aged five-six years old from a public pre-school located in Natal-RN, Brazil. The study highlights mediation acts of argumentative nature such as direct question; illustrations from the book; rereading that were used by the teacher-researcher in story discussion. Among its conclusions it is revealed that argumentative action in stories discussion favors and intensifies the agreement of children´s to the activity. It increases the interaction between text and reader; it favours children´s organization and explicitation of their thoughts. The analysed material shows children´s exposing their ability to argue when having adequade scaffolding by an argumentative mediator the teacher